Implikasi Pertarungan Hukum Hasan Azhari VS Gojek Tokopedia bagi Ekosistem Startup Indonesia - Fatin, Kayla Alima; Dewi, Tiwi Ayu Haresa; Hanif N, Fakhri; Klarisa, Agnes Widya; Tarina, Dwi Desi Yayi (Media Hukum Indonesia (MHI), 2024)
The legal case between Hasan Azhari and PT Goto Gojek Tokopedia Tbk, along with Nadiem Makarim, the Minister of Education and Culture, emerged after Hasan filed a lawsuit worth IDR 41.91 trillion in the Central Jakarta Commercial Court. In his lawsuit, Hasan accused the defendants of copyright infringement concerning a written work and computer program he claimed to have created, which served as the foundation for an online motorcycle taxi ordering method he developed in 2008. He sought compensation for lost revenue and royalties from Gojek's income in 2020 and 2021. This is not Hasan's first lawsuit; in 2021, he also filed a similar claim against Gojek for IDR 24.9 trillion, which the court subsequently dismissed. The case highlights crucial issues within Indonesia's startup ecosystem, particularly regarding copyright protection and its impact on innovation. Many experts have expressed skepticism about the claim, noting that the online motorcycle taxi business model has been widely adopted by various companies globally. The implications of this case for Indonesia's startup ecosystem are significant. If the lawsuit is upheld, it could set a dangerous precedent for innovation and the development of new businesses, given the legal risks that technology companies operating in similar domains might face. Furthermore, the case underscores the need for clear copyright regulations to ensure they do not hinder the growth of the creative and technology industries in Indonesia.